Topical Flagellin-Mediated Innate Defense against Candida albicans Keratitis - Gao, Nan (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. This study was conducted to investigate whether flagellin, the sole ligand of Toll-like receptor-5 (TLR5), induces an innate defense that is sufficient to protect injured corneas from Candida albicans. METHODS. Scarified corneas of adult B6, TLR5(−/−), Camp(−/−) (cathelicidin-related antimicrobial peptide), or PMN-depleted mice were pretreated with Pseudomonas aeruginosa flagellin or a mutant and then were inoculated with C. albicans. The corneas were compared for disease progression, cytokine and Camp expression, and PMN infiltration before and after C. albicans infection. Disease progress was recorded by digital photography and clinical scoring, cytokine levels were determined by ELISA, the levels of Camp gene product were assessed by Western blot, and PMN infiltration was measured by MPO determination and immunohistochemistry. RESULTS. Topical application of flagellin induced profound protection against Candida keratitis in a TLR5-dependent manner. The improved disease outcome including reduced tissue inflammation and rapid functional recovery can be attributed to a marked decrease in fungal burden at the early stage of C. albicans infection in flagellin-exposed B6 mouse corneas. Although both PMN infiltration and Camp upregulation contributed to corneal innate defense against fungal infection, Camp ablation totally, and PMN depletion partially, abrogated flagellin-induced fungal clearance in B6 mouse corneas. CONCLUSIONS. Flagellin induces a strong innate defense and promotes robust resistance to C. albicans infection in the cornea. Topical flagellin or its mimetic may become a new prophylactic agent for preventing contact lens or trauma/injury-associated microbial keratitis.